Acoustic tracking of a threatened juvenile shark species, the smooth hammerhead (Sphyrna zygaena), reveals vulnerability to exploitation at the boundary of a marine reserve - Albano, Patricia S.; Fallows, Chris; Fallows, Monique; Williams, Lacey H.; Murray, Taryn; Sedgwick, Oliver; Hammerschlag, Neil (Frontiers in Marine Science, 2023)
The coastal waters of South Africa are habitat to a diverse composition of sharks that are vulnerable to exploitation, many of which are endemic and/or classified by the International Union for Conservation of Nature (IUCN) Red List as Threatened or Data Deficient. Accordingly, this region has been identified as a global research and conservation priority for elasmobranchs. The De Hoop Marine Protected Area (MPA), in the Western Cape Province of South Africa, provides 288 km2 of no-take protection within its boundaries. However, the region experiences heavy commercial fishing, with two vessels actively operating as dedicated shark longliners (as of 2022). When crossing MPA boundaries, sharks are susceptible to capture by these vessels. Utilizing passive acoustic telemetry, the present study evaluated the movements of a threatened juvenile shark species, the smooth hammerhead (Sphyrna zygaena), both inside and adjacent to the De Hoop MPA, and along the greater coastline. Movement data from 20 tagged sharks were used to explore the effects of spatial, environmental, and management variables on their residency and movement patterns. Results indicate a high reliance of sharks on unprotected waters immediately adjacent to the MPA’s eastern boundary, an area of high biological productivity due to its proximity to the mouth of an estuary. Although some tagged sharks did move regionally along the South African coastline, individuals spent 95% of their days detected just outside the eastern boundary of the MPA, rendering them vulnerable to commercial shark longlining occurring there. These findings have conservation implications for smooth hammerhead sharks in South Africa and present an opportunity to revisit management practices that may optimize spatial protection for an important life stage of this threatened species.